anonymous
  • anonymous
y = x - 2 y = 4x + 1 Solving systems by substitution .
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
just put the value of y from the first equation in second: x-2=4x+1 solve it for x put value of x in any original equation - you will have y. Let me know if there is any questions
anonymous
  • anonymous
how do i solve for x ?
anonymous
  • anonymous
x-2=4x+1 put all x on one side: 4x-x+1=-2 -1 from both sides: 3x=-3 divide both sides by (3): x=-1 now, you put value of x say in first equation: y=x-2=-1-2=-3 so, y=-3 your answer should be: x=-1, y=-3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
thank you so much !

Looking for something else?

Not the answer you are looking for? Search for more explanations.